The Influence of Social Media Marketing, Facilities, Location, and Trust on The Decision To Stay at Midtown Residence Surabaya - Yodha, Meilani Putri; Indrawati, Lilik (UKMC International Conference (UKMC IC) Proceedings, 2024)
Currently, the business world, particularly in the service sector, has developed significantly. One of the growing service industries in Indonesia is tourism. The tourism industry certainly requires accommodations, one of which is lodging. Over time, Surabaya has seen an increase in the number of hotels ranging from 1 star to 5 star establishments. one of the four star hotels in Surabaya is Midtown Residence Surabaya. This research aims to determine whether social media marketing, facilities, location, and trust have an impact on the decision to stay at Midtown Residence Surabaya. This study is conducted quantitatively with data collection using questionnaires and analyzed using SPSS 26. The sample for this study consists of 100 respondents, with purposive sampling used for sample selection. Based on the data analysis results, the study shows that social media marketing does not affect the decision to stay, whereas facilities, location, and trust significantly influence the decision to stay.